2014
DOI: 10.1111/jam.12679
|View full text |Cite
|
Sign up to set email alerts
|

Composition of diet modifies colonization dynamics ofCampylobacter jejuniin broiler chickens

Abstract: Our study proves that diet composition can modify Camp. jejuni colonization depending on sampling time point postinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 35 publications
4
33
1
Order By: Relevance
“…Acetate is an SCFA metabolite produced as a by-product by commensal bacteria and is most abundantly found in the lower intestinal tracts of many hosts, including avian species (29, 30). Other SCFAs, such as butyrate and propionate, are also produced by commensals and commonly found in the same intestinal regions as acetate.…”
Section: Resultsmentioning
confidence: 99%
“…Acetate is an SCFA metabolite produced as a by-product by commensal bacteria and is most abundantly found in the lower intestinal tracts of many hosts, including avian species (29, 30). Other SCFAs, such as butyrate and propionate, are also produced by commensals and commonly found in the same intestinal regions as acetate.…”
Section: Resultsmentioning
confidence: 99%
“…This link can also be explained by the fact that the Clostridium organic acid production could be used by C. jejuni as an energy source. Furthermore, it was found that a Campylobacter infection induces excess mucous production in the intestine (Molnár et al, 2015) which consequently may enhance Clostridium proliferation due to the fact that an increase in mucin secretion in the gut provides an opportunity for Clostridium spp. to proliferate (M'Sadeq et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Changing poultry diet may modify the caecal microbiota and gut health of chicken, and therefore may affect the colonization pattern of C. jejuni [11, 12]. Recent studies have shown that maize- or wheat-based diets, which contain different levels of crude protein, can alter the viscosity of gut content and histomorphology of the chicken gut [11], and subsequently reduce C. jejuni colonization in broilers [9].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that maize- or wheat-based diets, which contain different levels of crude protein, can alter the viscosity of gut content and histomorphology of the chicken gut [11], and subsequently reduce C. jejuni colonization in broilers [9]. Changes in diet due to different protein sources or non-antibiotic feed additive may modify the gastrointestinal environment creating disturbances in the resident microbiota thus allowing—directly or indirectly—either a proliferation or reduction of bacterial pathogens [10, 55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation